2019
DOI: 10.3390/vaccines7010021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immune Responses to Different Versions of VLP Associated Stabilized RSV Pre-Fusion F Protein

Abstract: Efforts to develop a vaccine for respiratory syncytial virus (RSV) have primarily focused on the RSV fusion protein. The pre-fusion conformation of this protein induces the most potent neutralizing antibodies and is the focus of recent efforts in vaccine development. Following the first identification of mutations in the RSV F protein (DS-Cav1 mutant protein) that stabilized the pre-fusion conformation, other mutant stabilized pre-fusion F proteins have been described. To determine if there are differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(71 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…For presentation of pre-fusion F protein on the surfaces of VLPs, the pre-fusion stabilizing DS-Cav1 pre-fusion F with or without foldon domain was fused to the TM of NDV F protein [99]. A recent study reported that NDV VLPs containing pre-fusion F stabilized single chain F with deletions of the peptide 27 sequence and cleavage sites and point mutations could induce higher RSV neutralizing antibodies in cotton rats, compared to NDV VLP with DS-Cav1 F [100].…”
Section: Rsv Vlp Vaccine Components and Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…For presentation of pre-fusion F protein on the surfaces of VLPs, the pre-fusion stabilizing DS-Cav1 pre-fusion F with or without foldon domain was fused to the TM of NDV F protein [99]. A recent study reported that NDV VLPs containing pre-fusion F stabilized single chain F with deletions of the peptide 27 sequence and cleavage sites and point mutations could induce higher RSV neutralizing antibodies in cotton rats, compared to NDV VLP with DS-Cav1 F [100].…”
Section: Rsv Vlp Vaccine Components and Platformsmentioning
confidence: 99%
“…RSV pre-fusion stabilizing mutations (DS-Cav1) with a foldon stabilizer retained pre-F site Ø epitopes and site II neutralizing epitopes in soluble proteins [136]. It is likely that additional mutations together with DS-Cav1 or alternative mutations in RSV F will be required for further stabilization of pre-fusion F protein antigens on VLP platforms [99,100]. RSV F nanoparticle formulations of recombinant F proteins produced in the insect cell expression system are under advanced clinical trials of maternal vaccination to protect infants although the vaccine phase III clinical trial in the elderly was not successful [132,133,137].…”
Section: Rsv and Hmpv Vlp Vaccinesmentioning
confidence: 99%
“…A very important question for vaccine development is whether the different mutation-stabilized pre-fusion F proteins are indeed the same in terms of structure, antibodies induced, and protection from RSV challenge afforded by their use as immunogens. We have recently addressed these questions by comparing the reactivity to monoclonal antibodies and the immunological properties of virus-like particles (VLPs) assembled with different versions of mutation-stabilized pre-fusion F proteins [18,30]. We have reported that five different pre-fusion F proteins, in VLPs, bind differently to representative pre-fusion specific monoclonal antibodies (mAb) [18].…”
mentioning
confidence: 99%
“…We have recently addressed these questions by comparing the reactivity to monoclonal antibodies and the immunological properties of virus-like particles (VLPs) assembled with different versions of mutation-stabilized pre-fusion F proteins [18,30]. We have reported that five different pre-fusion F proteins, in VLPs, bind differently to representative pre-fusion specific monoclonal antibodies (mAb) [18]. Compared to VLPs assembled with DS-Cav1 F protein, two of these alternative mutation-stabilized pre-fusion F protein VLPs induced, in mice, neutralization titers 3 to 4-fold higher than DS-Cav1 F VLPs [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation